Magnetic Resonance Imaging evidence of Inflammation at Interphalangeal joint of Thumb — A distinct entity in psoriatic arthritis. (28th June 2021) - Mathew, Ashish J; Ganapati, Arvind; Panwar, Jyoti; Koshy, Varghese; Desai, Anu; Danda, Debashish
Abstract: Background: This study aimed to compare inflammation at the interphalangeal (IP) joint of thumb in patients with psoriatic arthritis (PsA), rheumatoid arthritis (RA), undifferentiated inflammatory arthritis (UIA), and in psoriasis patients without clinical arthritis (PsO) using low‐field magnetic resonance imaging (MRI). Methods: Age‐matched and disease duration‐matched patients with inflammatory arthritis (RA, PsA, and UIA) and psoriasis patients without clinical arthritis (PsO), who had undergone MRI of hands were included in this study. The presence or absence of MRI inflammatory lesions including synovitis, tenosynovitis, and bone marrow edema was assessed by three independent readers. Agreement between the readers was assessed using the intraclass correlation coefficient. Risk ratio of MRI global inflammation around thumb IP joints among patients with PsA was compared with the other groups. Results: Clinical parameters and MRI inflammation were studied in 161 patients (42 PsA, 28 RA, 29 UIA, and 62 PsO). Global MRI inflammation at the IP joint of the thumb was observed in 33.3% of PsA patients compared with 14.3% in RA, and 10.3% in UIA. Subclinical MRI inflammation was observed in 8.1% of patients with PsO. The risk ratios of MRI global inflammation at the IP joint of the thumb in PsA patients were 2.3 (95% confidence interval [CI] 0.86‐6.36) and 3.2 (95% CI 1.02‐10.21) compared with RA and UIA patients, respectively. Conclusion: Global MRI inflammation around the IP joint of the thumb is significantly more common in patients with PsA as compared to individuals with UIA.